Dynamics of shear band instabilities in cutting of metals. Issue 1 (2019) - Yadav, Shwetabh; Feng, Gan; Sagapuram, Dinakar
Abstract: We study the dynamics of flow instability and shear localization in cutting using direct high-speed imaging and low melting point alloy as a model material system. The onset of instability and departure from steady laminar flow is triggered by nucleation of shear band at the tool tip and subsequent propagation towards the free surface. The stress at the onset of shear band formation is found to be constant and a physical characteristic of the material. The shear band velocity and inhomogeneous strain field arising from the banding are quantitatively characterized using an image correlation method.